1972
DOI: 10.1073/pnas.69.12.3501
|View full text |Cite
|
Sign up to set email alerts
|

Mutants That Produce Nitrogenase in the Presence of Ammonia

Abstract: Rhizobium-legume symbionts and all Nrfixing bacteria and Nrfixing blue-green algae that have been examined exhibit a striking level of repression of nitrogenase synthesis when excess NH4+ is added to the growth medium (for example, refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Duplicated segments, which are cis and tandem to the original loci, are known to be unstable (Novick, 1969), in contrast to duplicated integrations which are stabilized by genetic inversion (Adelberg & Bergquist, 1972 (Shah, Davis & Brill, 1972). By selecting re\ ertants of an Azotobacter mutant unable to synthesize any component of nitrogenase, Gordon & Brill (1972) isolated constitutive mutants, which produced nitrogenase in the presence of NH,'. We have observed that the Escherichia coli Nif-hybrid, C -~7 , produces a niirogenase with the same physiological properties as that of the Klebsiella donor strain.…”
Section: Nitrogen Jixatioti Gmes Ill E Coli 237mentioning
confidence: 99%
“…Duplicated segments, which are cis and tandem to the original loci, are known to be unstable (Novick, 1969), in contrast to duplicated integrations which are stabilized by genetic inversion (Adelberg & Bergquist, 1972 (Shah, Davis & Brill, 1972). By selecting re\ ertants of an Azotobacter mutant unable to synthesize any component of nitrogenase, Gordon & Brill (1972) isolated constitutive mutants, which produced nitrogenase in the presence of NH,'. We have observed that the Escherichia coli Nif-hybrid, C -~7 , produces a niirogenase with the same physiological properties as that of the Klebsiella donor strain.…”
Section: Nitrogen Jixatioti Gmes Ill E Coli 237mentioning
confidence: 99%
“…Regulatory mutants of nif in A. vinelandii include those which lack the ability to synthesise both MoFe and Fe proteins under derepressing conditions (Shah et al 1973); those which synthesise nitrogenase constitutively in NH4+ (Gordon and Brill 1972); and an interesting mutant (UW38), having no parallel in K. pneumoniae, which fails to make MoFe protein but overproduces Fe protein .…”
Section: Regulation Of Nif Genes In Other Speciesmentioning
confidence: 99%
“…Studies with mutants unable to assimilate added NH: into glutamine, or inhibition of this process by methionine sulphoximine (MSX), have shown that repression of nif'by NH,+ requires its assimilation into glutamine (Gordon & Brill, 1972).…”
Section: Introductionmentioning
confidence: 99%